Training Needs Management (Case Study At The North Sumatra Province Human Resources Development Agency) - Suriyadi, Suriyadi; Wijaya, Candra; Mardianto, Mardianto (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The aim of this research is to discuss training needs management (case study at the Human Resources Development Agency of North Sumatra Province). This research uses a qualitative approach with descriptive methods. Data collection techniques use interview techniques, observation, and document study, while to strengthen validity, use credibility, transferability, dependability, and comfirmability. The results of this research are: (1) Training needs management is carried out using various methods and processes; the initial steps taken are planning, analyzing, and identifying these needs, which are also integrated with the North Sumatra province strategic plan to support the achievement of the North Sumatra vision and mission. The North Sumatra provincial HR development agency also develops training programs based on identified needs, such as developing training methods, selecting programs, collaborating with external parties, and evaluating programs that have been implemented previously. and there is also ineffective or inefficient communication regarding training needs, which can also lead to delays in information gathering or inappropriate coordination. (3) The model implemented by the North Sumatra provincial HR development agency regarding training needs management begins with identifying training needs, determining quality, training planning, training implementation, training evaluation, monitoring and improvement, reporting and transparency, career development, training needs data management, and stakeholder involvement. The above model of course management of training needs will be implemented more effectively if all the systems and models that have been designed work well.